2010
DOI: 10.1016/j.ejvs.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Spinal Cord Ischaemia Following Thoracic and Thoracoabdominal Aortic Endovascular Intervention

Abstract: SCI following thoracic and thoracoabdominal aortic endovascular intervention is associated with the proportion of aorta covered. The degree of risk varies between different types of procedure and this should be carefully considered in both selection and consenting of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…4,7-12 Comparing outcomes after thoracic aortic endovascular interventions can be difficult, however, given the heterogeneity of the procedures performed. Drinkwater et al 16 recently demonstrated a significant rise in the risk of SCI with increasing magnitude of procedure type; TEVAR (stent graft confined to the thoracic aorta) was associated with the least risk at 1.8%; arch hybrid 10%, fenestrated/branched graft 14.3%, and visceral hybrid 20%. Although we aimed to maximize validity by intentionally choosing to focus on a single procedure type, we also observed an increase in the incidence of SCI within our excluded patient subgroups; The extent of neurologic deficits attributed to SCI after TEVAR can range from mild paraparesis to flaccid paralysis.…”
Section: Discussionmentioning
confidence: 96%
“…4,7-12 Comparing outcomes after thoracic aortic endovascular interventions can be difficult, however, given the heterogeneity of the procedures performed. Drinkwater et al 16 recently demonstrated a significant rise in the risk of SCI with increasing magnitude of procedure type; TEVAR (stent graft confined to the thoracic aorta) was associated with the least risk at 1.8%; arch hybrid 10%, fenestrated/branched graft 14.3%, and visceral hybrid 20%. Although we aimed to maximize validity by intentionally choosing to focus on a single procedure type, we also observed an increase in the incidence of SCI within our excluded patient subgroups; The extent of neurologic deficits attributed to SCI after TEVAR can range from mild paraparesis to flaccid paralysis.…”
Section: Discussionmentioning
confidence: 96%
“…3 The reported incidence of SCI ranged between 0% and 10% for thoracic endovascular aortic repair (TEVAR) and between 0% and 30% for endovascular TAAA repair. 4 Comparably, the "real-world" incidence of SCI after open TAAA repair still ranges between 5% and 11% for all types of TAAAs and up to 22% for Crawford type II TAAAs. 4 Of note, several centers of excellence have reported SCI rates after open surgical repair of Crawford type II TAAAs of <4%.…”
mentioning
confidence: 98%
“…4 Comparably, the "real-world" incidence of SCI after open TAAA repair still ranges between 5% and 11% for all types of TAAAs and up to 22% for Crawford type II TAAAs. 4 Of note, several centers of excellence have reported SCI rates after open surgical repair of Crawford type II TAAAs of <4%. 5 In contrast to open repair, in which the refinement of the surgical technique and the adoption of several adjunctive measures led to a significant reduction of SCI, the literature on endovascular TAAA repair lacks evidence about specific interventions or measures that warrant routine spinal cord monitoring and perfusion.…”
mentioning
confidence: 98%
“…In a report investigating spinal cord ischemia during thoracic aortic procedures between 2001 and 2009, the global incidence rate was found to be nearly 1 in 10 [2]. Despite the pressing need to better understand SCII, very little is known regarding the pathological mechanisms underlying its detrimental impacts.…”
Section: Introductionmentioning
confidence: 99%